Propofol Reduces Lipopolysaccharide-Induced, NADPH Oxidase (NOX2) Mediated TNF-α and IL-6 Production in Macrophages - Tao Meng; Jingya Yu; Zhen Lei; Jianbo Wu; Shuqin Wang; Qiyu Bo; Xinyu Zhang; Zhiyong Ma; Jingui Yu (Clinical and Developmental Immunology)
During an infection, lipopolysaccharide (LPS) stimulates the production of reactive oxygen species (ROS), which is mediated, in large part, by nicotinamide adenine dinucleotide phosphate (NADPH) oxidases (NOXs); NOX2 is the major NOX isoform found in the macrophage cell membrane. While the immunomodulatory activity of propofol is highly documented, its effect on the LPS-induced NOX2/ROS/NF-κB signaling pathway in macrophages has not been addressed. In present study, we used murine macrophage cell line RAW264.7 pretreated with propofol and stimulated with LPS. IL-6 and TNF-α expression, ROS production, and NOX activity were determined. Results showed that propofol attenuated LPS-induced TNF-α and IL-6 expression. Moreover, LPS-stimulated phosphorylation of NF-κB and generation of ROS were weakened in response to propofol. Propofol also reduced LPS-induced NOX activity and expression of gp91phox and p47phox. We conclude that propofol modulates LPS signaling in macrophages by reducing NOX-mediated production of TNF-α and IL-6.